Underserved Pregnant and Postpartum Women's Access and Use of Their Health Records. Issue 3 (May 2018) - Guo, Yuqing; Hildebrand, Janet; Rousseau, Julie; Brown, Brandon; Pimentel, Pamela; Olshansky, Ellen
Abstract: Purpose: The purpose of this study was to examine knowledge of and experiences with use of their electronic health record (EHR) among mostly Hispanic women during pregnancy and postpartum. Methods: Women who were in the MOMS Orange County prenatal or postpartum home visitation program completed surveys and participated in focus groups. Descriptive and content analyses were used. Results: Twenty-six women participated. Nearly all women (24, 92.3%) knew what health records were and most (80.8%) felt that keeping their records would increase or greatly increase their confidence in caring for themselves and their families. Approximately one third reported already keeping a copy of their health records. Common barriers to accessing and understanding health records included healthcare providers' noncompliance with the Health Information Technology for Economic and Clinical Health Act, limited EHR adoption, unfriendly patient portals, complicated medical terminology, rushed appointments with healthcare providers, lack of Spanish interpreters, and lack of Spanish-speaking healthcare providers. Clinical Implications: Programs are needed to educate and support women and providers in using health records to promote health literacy, pregnancy management, and patient–provider relationships in underserved populations. Abstract : Electronic health portals are becoming more common as part of pediatric and maternity care. In this study, access and use of health records among underserved pregnant and postpartum women is examined and suggestions for clinical practice recommendations based on findings are presented.